Capacitação em boas práticas de manipulação de alimentos como ferramenta para a educação sanitária: revisão sistemática - Traldi Junior, José Sérgio (2021)
The Sanitary Surveillance of food is understood in the SUS and presents a fundamental role to ensure the quality of food consumed by the population and consequently in the prevention of foodborne diseases. In this context, health education through training in good handling practices for food handlers is an important tool for health prevention, protection and promotion. The aim of the study is to present results in relation to training in good food handling practices, discussing the results, reporting potentialities and limits based on previous experiences and proposing an educational intervention. This is a qualitative and descriptive research, developed from the systematic review of studies that addressed health education through training in good food handling practices of employees working in the food area. Based on the problem and hypotheses, an inquiring question was elaborated and the Matrix of PICOS was constructed that comprises the population (P), intervention (I), comparison (C), outcome (O) and type of study (S). Subsequently, searches were performed in the health databases using DeCS related to the PICOS matrix, and a total of 203 studies were found, of which 25 were selected according to the inclusion and exclusion criteria. The systematization of the selected studies began with the construction of a visualization matrix and later the data analysis through registration and elaboration of analytical matrix. The studies were grouped according to the similarities and discrepancies and through the floating reading a reflection was carried out on the evidence pointed out in the experiences of training in good practices of food manipulation and connection with reality in the municipal Sanitary Surveillance. The discussion was divided into 4 thematic nuclei: importance of educational intervention in the hygienic-sanitary quality of food; good handling practices; training in good handling practices; knowledge x behavior change. It can be observed that training is a very important tool to qualify handlers and presents promising results. Although there is still no consensus on the ideal didactic model to use during these educational interventions and not all of them demonstrated positive results, it is noted that the different techniques used showed interesting results and should be considered to stimulate health education and consequently promote food security. Thus, the present work seeks to present evidence that may be important for the construction of educational interventions aimed at food handlers.